Secondary students' perceptions of the importance, difficulty, interest and engagement in learning biology - Chan, Chiew Wair (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study aims to provide a glimpse ofMalaysian secondary school students' perceptions on biology content, their importance, difficulties, interests and engagement in learning. Biology is a subject that has often been considered as difficult by students. Biology contents refer to the topics that students learned according to the curriculum. Based on previous studies, there has been a decline in interest in learning science, including Biology in many countries. Therefore, this study highlighted students' perceptions toward biology content from the aspect of importance, difficulties, interests and engagement in learning, as well as exploring a possible gender difference in their attitudes. A questionnaire was used to measure students' perceptions on the importance, difficulty, interest and engagement in learning biology content of 356 form five students in the district Sibu, Sarawak, Malaysia. Results showed that the secondary students perceived importance for all the topics in form four biology content. In addition, the findings indicated that they found the content as moderately difficult. Nonetheless, the students found learning biology moderately interesting. There was a positive relationship between student engagement in learning and perceptions of the importance, as well as an interest in learning biology content. However, there was a negative relationship between student engagement in learning and perceptions of the difficulty in learning biology. Gender did not have an impact on students' perceptions of the importance, difficulty, interest and engagement in learning biology content.